Comprehensive Analysis of Bacterial Communities and Microbiological Quality of Frozen Edible Insects - Sasiprapa Krongdang; Nipitpong Sawongta; Jintana Pheepakpraw; Achirawit Ngamsomchat; Sutee Wangtueai; Jittimon Wongsa; Thanya Parametthanuwat; Narin Charoenphun; Thararat Chitov (Foods)
Edible insects are gaining traction worldwide; however, the existing data regarding their microbiological quality remain inadequate. This study investigated the bacterial communities and microbiological quality of five types of frozen edible insects commercially available in Thailand. Amplicon sequencing revealed Firmicutes (Bacillota) and Proteobacteria (Pseudomonadota) as the main phyla across all samples; Bacteroidota was predominant in house crickets, Actinobacteriota in silkworms, and Desulfobacterota was exclusively found in house and mole crickets. Culture-based assays showed total viable counts, lactic acid bacteria, yeasts–molds, and spore-formers ranging from 3.41–6.58, 2.52–7.41, 1.83–5.62, to 2.00–4.70 log CFU·g−1, respectively. In some samples, Enterobacteriaceae and Escherichia coli, key hygiene indicators, reached 5.05 and 2.70 log CFU·g−1, respectively. Among foodborne pathogens, presumptive Bacillus cereus was found to vary from <1.70 to 3.93 log CFU·g−1, while Clostridium perfringens and Staphylococcus aureus were under the quantitation limit, and Salmonella was absent. Overall, the results indicate significant variation in microbial diversity and quality among different insect types. The high levels of microbial hygiene indicators and foodborne pathogens in some samples raised food safety concerns and point to the need to develop or implement production guidelines and microbiological criteria for frozen edible insects to ensure food safety.